EFFECTIVENESS OF BUERGER ALLEN EXERCISE ON ABI VALUES AND BLOOD SUGAR LEVELS IN TYPE 2 DM PATIENTS AT THE DIABETES CLINIC IN SOUTH TANGSEL CITY - Fitriani, Dewi; Holidah, Holidah; Mustiyawati, Mustiyawati (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2025)
ABSTRACTAccording to the American Diabetes Association (ADA) in 2020, diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, impaired insulin work or both. The most common diabetes mellitus experienced by people in the world is Type 2 DM (85-95%). Indonesia is one of the Southeast Asian countries included in this ranking. It is predicted that Indonesia will have a significant increase in the prevalence of DM in the world. The increase in Type 2 DM patients has a major influence on the increase in complications. Complications of Type 2 DM include Peripheral Arterial Disease (PAD). PAD is the formation of atherosclerosis due to thickening of the basement membrane of large and small blood vessels in the peripheral arterial blood flow in the lower extremities. The aim of the research is to determine the effectiveness of the Buerger Allen Exercise on ABI values and blood glucose levels during Type 2 DM patients at the Diabetes Connection and Care Clinic. This research method is quantitative, this type of research is quasi-experimental, the research design is pretest-posttest with control group with the Peired t-test and the independent test. Total population was 80 respondents with the sampling technique being total sampling, 40 respondents in the intervention group and 40 respondents in the control group. The research was conducted for 2 consecutive weeks. The results of the study showed an increase in ABI values in the intervention group and control group where the p value was less than p 0.05 and there was a decrease in blood sugar levels in the intervention and control groups where the p value was less than p 0.05. However, the difference in improvement in the intervention group was higher than the control group. The results of the independent sample t-test statistical test for the ABI value obtained a p value ≤ 0.05 (p=0.000) and it can be concluded that the statistical test for the intervention group and the control group was significant. The results of the independent sample t-test statistical test for blood sugar levels when obtained p value ≤ 0.05 (p=0.018) it can be concluded that the statistical tests for the intervention group and control group are significant. From these results it can be concluded that the Buerger Allen Exercise is effective in increasing ABI values and reducing blood sugar levels at any time. It is hoped that this research will increase knowledge and this research can be used as study material to develop further research.                                                      ABSTRAKABSTRAK Menurut American Diabetes Association (ADA) tahun 2020, diabetes melitus adalah suatu kelompok penyakit metabolik dengan karakteristik hiperglikemia yang terjadi karena kelainan sekresi insulin, gangguan kerja insulin atau keduanya. Diabetes Melitus paling banyak dialami oleh penduduk di dunia adalah DM Tipe 2 (85-95%). Indonesia merupakan salah satu negara Asia Tenggara yang masuk dalam peringkat ini, diprediksi bahwa Indonesia memiliki penigkatan prevalensi DM yang signifikan di dunia. Kenaikan pasien DM Tipe 2 ini memiliki pengaruh besar pada peningkatan komplikasi. Komplikasi DM Tipe 2 diantaranya adalah Peripheral Arterial Disease (PAD). PAD adalah terbentuknya Aterosklerosis akibat penebalan membran basal pembuluh darah besar dan kecil pada aliran darah arteri perifer di ektermitas bawah. Tujuan penelitian Mengetahui efektivitas Buerger Allen Exercise terhadap nilai ABI dan kadar glukosa darah sewaktu pada Pasien DM Tipe 2 di Klinik Diabetes Connection and Care. Metode Pnelitian ini adalah kuantitatif, jenis penelitian ini Quasy Eksperimental yang desain penelitiannya pretest-posttest with control group dengan Uji Peired t-test dan Uji Independentt-test. Jumlah Populasi 80 responden dengan teknik pengambilan sampel adalah total sampling, 40 responden kelompok intervensi dan 40 responden kelompok kontrol. Penelitian dilakukan selama 2 minggu berturut turut. Hasil penelitian terdapat peningkatan nilai ABI pada kelompok intervensi dan kelompok kontrol dimana nilai p kecil dari p 0,05 dan terdapat penurunan kadar gula darah sewaktu pada kelompok intervensi dan kontrol dimana nilai p kecil dari p 0,05. Tetapi untuk selisih peningkatan kelompok intervensi lebih tinggi dibandingkan kelompok kontrol. Hasil uji statistik independen sample t-test untuk nilai ABI diperoleh nilai p value ≤ 0,05 (p=0,000 ) dapat disimpulkan bahwa uji statistik kelompok intervensi dan kelompok kontrol bermakna.Hasil uji statistik independen sample t-test untuk kadar gula darah sewaktu diperoleh nilai p value ≤ 0,05 (p=0,018 ) dapat disimpulkan bahwa uji statistik kelompok intervensi dan kelompok kontrol bermakna. Dari hasil tersebut dapat disimpulkan bahwa Buerger Allen Exercise efektif dalam meningkatan nilai ABI dan menurunkan kadar gula darah sewaktu. Saran Penelitian ini diharapkan dapat menambah pengetahuan dan penelitian ini dapat dijadikan sebagai bahan kajian untuk mengembangkan penelitian selanjutnya.